15th International Symposium on Software Reliability Engineering
DOI: 10.1109/issre.2004.18
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Studies of Test Case Prioritization in a JUnit Testing Environment

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Since mutation score is used as an indicator of good quality test cases, using it in test case prioritization gives higher priority to test cases that have a higher chance of exposing faults. Do et al [57] designed and performed an experiment on Java programs that are tested under JUnit framework. They have found that test case prioritization improves the rate of fault detection for JUnit test suites.…”
Section: Related Workmentioning
confidence: 99%
“…Since mutation score is used as an indicator of good quality test cases, using it in test case prioritization gives higher priority to test cases that have a higher chance of exposing faults. Do et al [57] designed and performed an experiment on Java programs that are tested under JUnit framework. They have found that test case prioritization improves the rate of fault detection for JUnit test suites.…”
Section: Related Workmentioning
confidence: 99%
“…Table 2 shows the maximum, mean, and minimum sizes of these test suites. We followed existing work (Do et al 2004;Elbaum et al 2002;Mei et al 2011) to exclude a faulty version from data analyses if more than 20 percent of the test cases detected the fault from the version. The numbers of faulty versions actually used are shown in the rightmost column of Table 1.…”
Section: Benchmark and Test Suitesmentioning
confidence: 99%
“…Regression testing can be more effective by selecting only those test cases relevant to the modified components. Test case prioritization is one of major tasks in regression testing, enabling test cases to be executed in selected order to achieve specific testing purposes, such as a higher fault detection rate (Do et al 2004;Elbaum et al 2002;Srivastava and Thiagarajan 2002). Leung and White (1989) provided a principle of retests by dividing the regression testing problem into two subproblems: test selection and test plan update.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…A priori knowledge about the characteristics of tests which are more likely to detect a defect is useful for test case prioritisation. In regression testing, test case prioritisation determines which tests should be executed first to potentially improve the defect detection rate [8]. Various prioritisation techniques have been proposed in the literature [20,41], one of which is total function coverage.…”
Section: Introductionmentioning
confidence: 99%